The ius commune in England : four studies - Helmholz, R. H. (Oxford University Press, 2001)
The ius commune is the amalgamation of Roman and canon laws on the continent. This work addresses the ius commune's relation to and influence on English law. The author begins by observing that there were many overlapping areas between English institutions. Through four studies (the law of sanctuary, the law of compurgation, mortuaries and the law of custom, and civil jurisdiction and the clergy), he draws out the coincidences between English law and the ius commune and shows where they developed parallel bodies of doctrine. Helmholz aims to fill some of the gaps in scholarship on the common legal past of Western law, the history of the Roman and canon laws, the history of the ecclesiastical courts, parallels between the ius commune and English common law, and English church history.